Effect of minimum wages on labor, welfare and economic growth: Evidence from East Java province - Rizal, Mohammad; Mustapita, Arini Fitria (Optimum: Jurnal Ekonomi dan Pembangunan, 2024)
Wage issues are still a major concern, especially in Indonesia. The fact that wages constitute the most significant part of a person's income makes it an important indicator that reflects the level of welfare of a country. The minimum wage policy also serves as a protective tool for companies to maintain labor productivity. This research analyze the relationship between minimum wages and the number of labor, welfare, and economic growth in East Java. East Java has a significant role in the number of labor, prosperity, and economic growth, making a major contribution to the national economy with a substantial workforce. This research uses a quantitative approach. The data analysis technique uses canonical correlation statistical techniques. The data used taken from the annual reports of each city/district for 2018-2022, totaling 38 regions. The number of labor, welfare, and economic growth can be predicted through the city/district minimum wage. Meanwhile, individually, the minimum wage has the relationship with the number of labor because wages are the primary motivation of workers. In addition, the minimum wage is related to the welfare of workers in East Java, and the minimum wage is related to economic growth.